Association of the triglyceride-glucose index with immunotherapy efficacy and long-term prognosis in advanced Non-small cell lung cancer - Ma, Lijie; Zhu, Wanling; Wang, Yulang; Zhao, Li; Wei, Xiangju; Xiong, Xianmin; Ji, Guijuan (Frontiers in Oncology, 2025)
BackgroundNon-small cell lung cancer (NSCLC), the most common subtype of primary lung cancer, represents a major component of the global cancer burden. Despite the availability of several immunotherapeutic and immune-combination treatment modalities, its prognosis remains poor. Therefore, it is particularly important to predict the prognosis of these patients.AimTo investigate whether a marker of insulin resistance [the triglyceride-glucose (TyG) index] could predict clinical outcomes in patients with advanced non-small cell lung cancer receiving pembrolizumab and chemotherapy.MethodsWe retrospectively analyzed data of 243 patients with advanced non-small cell lung cancer treated with pembrolizumab and chemotherapy, dividing them into high and low TyG index groups based on an optimal cut-off value of 1.61, determined using the X-tile software. Cox proportional hazards regression analysis identified independent prognostic factors for overall survival (OS), and a prediction nomogram model was developed based on them.ResultsThe study cohort included 132 patients with a high TyG index and 111 with a low TyG index. The median progression-free survival and OS in the low TyG index group were significantly longer than in the high TyG index group. The objective response rate was 45.05% in the low TyG index group and 25.76% in the high TyG index group, while the respective disease control rates were 85.59% and 53.03%. Multifactorial regression analysis identified pre-treatment maximum tumor diameter, PD-L1 TPS (Tumor Proportion Score), BMI(Body Mass Index), and TyG index as independent prognostic predictors of OS. The nomogram model emphasized the importance of the TYG index as a major prognostic predictor, followed by the PD-L1 TPS score, pre-treatment tumor diameter, and BMI.ConclusionThe TyG index is a long-term predictor of the efficacy of combined immunotherapy and chemotherapy in patients with advanced NSCLC. Patients with a low TyG index have a better prognosis.